Microwave pyrolysis of oily sludge with activated carbon. Issue 24 (16th December 2016) - Chen, Yi-Rong
ABSTRACT: The aim of this study is to explore catalytic microwave pyrolysis of crude oil storage tank sludge for fuels using granular activated carbon (GAC) as a catalyst. The effect of GAC loading on the yield of pyrolysis products was also investigated. Heating rate of oily sludge and yield of microwave pyrolysis products such as oil and fuel gas was found to depend on the ratio of GAC to oily sludge. The optimal GAC loading was found to be 10%, while much smaller and larger feed sizes adversely influenced production. During oily sludge pyrolysis, a maximum oil yield of 77.5% was achieved. Pyrolytic oils with high concentrations of diesel oil and gasoline (about 70 wt% in the pyrolytic oil) were obtained. The leaching of heavy metals, such as Cr, As and Pb, was also suppressed in the solid residue after pyrolysis. This technique provides advantages such as harmless treatment of oily sludge and substantial reduction in the consumption of energy, time and cost.